(untitled) (Bangladesh Journal of Botany, 2021)
Twenty species of fungi associated with blight symptom of different plant parts of Tagetes erecta L. and T. patula L. have been described. The associated fungi were Alternaria alternata (Fr.) Keissler, Aspergillus flavus Link, A. fumigatus Fresenius, A. niger van Tieghem, Bipolaris australiens is (M.B. Ellis) Tsuda &Ueyama, Chaetomium globosum Kunze, Cladosporium elatum (Harz) Nannf., Corynespora cambrensis M. B. Ellis, Curvularia brachyspora Boedijn, C. fallax Boedijn, C. lunata (Wakker) Boedijn, C. stapeliae(du Plessis) Hughes &du Plessis, Epicoccum purpuras cens Ehrenb. ex Schlecht, Fusarium semitectum Berk. & Rav., Monochaetia ceratoniae (Sousa da Camera) Sutton, Nigrospora panici Zimm., Penicillium italicum Wehmer, Rhizopus stolonifer (Ehrenb.: Fr.) Vuill, Trichoderma viride Pers. and Trichothecium roseum Link.